Effect of Phototherapy and Urocanic Acid Isomers on Natural Killer Cell Function - Gilmour, Jill W; Vestey, James P; George, Sheru; Norval, Mary (Journal of investigative dermatology, 1993)
Ultraviolet (UV) radiation suppresses a variety of immune responses but it is uncertain whether this action contributes to the effectiveness of phototherapy. Urocanic acid (UCA) has been proposed as a mediator of the immunologic effects of UV. On exposure the naturally occurring trans-isomer of UCA in the skin changes into the cis-isomer, which has been demonstrated to mimic many of the immunomodulatory effects of UV irradiation. Natural killer (NK) cells play an important role in several immunologic processes and published evidence indicates that their activity is altered by UV irradiation. To ascertain the effect on NK cells of phototherapy used in the treatment of psoriasis, modulation of NK activity in psoriatic patients undergoing broad-band UVB, narrow-band UVB, or psoralen plus (PUVA) regimens was examined. This was compared with NK cell activity in psoriatic patients treated with topical coal tar and in normal subjects receiving broad band UVB. The NK cell activity of psoriatic and normal subjects was the same over a wide range of effector to target cell ratios. Almost all patients undergoing phototherapy exhibited depressed NK cell activity during or after irradiation, although the timing of the depression varied between the lamps used and may be related to dose. However, patients treated with topical coal tar showed unchanged NK cell activity throughout the therapy. The effect of UCA isomers on NK cell activity in vitro was also determined. It was found that cis-UCA induced a dose-dependent suppression of NK cell activity in both patients and normal subjects, whereas trans-UCA had hardly any effect in either group. Thus it is possible that there may be a correlation between cis-UCA formation in the epidermis and the modulation of NK cell activity that occurs during phototherapy.